Fault deformation mechanisms and fault rocks in micritic limestones: Examples from Corinth rift normal faults. (August 2015) - Bussolotto, M.; Benedicto, A.; Moen-Maurel, L.; Invernizzi, C.
Abstract: A multidisciplinary study investigates the influence of different parameters on fault rock architecture development along normal faults affecting non-porous carbonates of the Corinth rift southern margin. Here, some fault systems cut the same carbonate unit (Pindus), and the gradual and fast uplift since the initiation of the rift led to the exhumation of deep parts of the older faults. This exceptional context allows superficial active fault zones and old exhumed fault zones to be compared. Our approach includes field studies, micro-structural (optical microscope and cathodoluminescence), geochemical analyses (δ 13 C, δ 18 O, trace elements) and fluid inclusions microthermometry of calcite sin-kinematic cements. Our main results, in a depth-window ranging from 0 m to about 2500 m, are: i) all cements precipitated from meteoric fluids in a close or open circulation system depending on depth; ii) depth (in terms of P/T condition) determines the development of some structures and their sealing; iii) lithology (marly levels) influences the type of structures and its cohesive/non-cohesive nature; iv) early distributed rather than final total displacement along the main fault plane is the responsible for the fault zone architecture; v) petrophysical properties of each fault zone depend on the variable combination of these factors. Highlights: We recognised six groups of structures in a range of depth between 0 and 2300 m. We inferred the P/T conditions of fault nucleation and evolution. Fluid-driven mass transfer through the fault, and fluid origin are documented. Role of lithology, depth, displacement in fault zone architecture is investigated.